2013
DOI: 10.1371/journal.pone.0082275
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Hyperlipidemia- and Diabetes-Induced Early-Stage Apoptosis and Late-Stage Renal Dysfunction via Administration of Fibroblast Growth Factor-21 Is Associated with Suppression of Renal Inflammation

Abstract: BackgroundLipotoxicity is a key feature of the pathogenesis of diabetic kidney disease, and is attributed to excessive lipid accumulation (hyperlipidemia). Increasing evidence suggests that fibroblast growth factor (FGF)21 has a crucial role in lipid metabolism under diabetic conditions.ObjectiveThe present study investigated whether FGF21 can prevent hyperlipidemia- or diabetes-induced renal damage, and if so, the possible mechanism.MethodsMice were injected with free fatty acids (FFAs, 10 mg/10 g body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 58 publications
9
70
0
2
Order By: Relevance
“…In a recent animal study, FGF21 administration markedly decreased urinary albumin excretion and mesangial expansion and improved renal lipid metabolism and oxidative stress injury in db/db mice [31]. In another study, diabetes-and hyperlipidaemia-induced renal damage was enhanced in Fgf21-knockout mice, but was prevented by exogenous FGF21 administration [32]. These studies suggest that FGF21 may play a role in diabetic nephropathy through its effect on glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent animal study, FGF21 administration markedly decreased urinary albumin excretion and mesangial expansion and improved renal lipid metabolism and oxidative stress injury in db/db mice [31]. In another study, diabetes-and hyperlipidaemia-induced renal damage was enhanced in Fgf21-knockout mice, but was prevented by exogenous FGF21 administration [32]. These studies suggest that FGF21 may play a role in diabetic nephropathy through its effect on glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, Kim et al (27) demonstrated that FGF21 protects the kidneys in a mouse model of type 2 diabetes by improving insulin sensitivity. Our previous study (56) also demonstrated the beneficial effect of FGF21 on type 1 diabetes-induced renal damage.…”
mentioning
confidence: 72%
“…A 180-kVp X-ray generator (Model XSZ-Z20/20, China) was used to deliver radiation at a dose rate of 12.5 mGy/min (120 kv, 13 mA). Diabetic mice in the DM/LDR and DM/Com groups received whole body irradiation every 2 days at a dose of 50 mGy/day for 4 wk, based on our previous observations (56). Mice in the DM/FGF21 or DM/Com groups were given intraperitoneal (ip) injections of 1.5 mg/kg FGF21 daily for 8 wk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [16] reported that thrombomodulin domain 1 ameliorates diabetic nephropathy in mice via suppressing the NF-κB/NLRP3 inflammasome-mediated inflammatory process. Recently, Zhang et al [17] reported that FGF-21 can significantly prevent diabetes-induced early-stage renal apoptosis, hypertrophy, and dysfunction, and significant prevented inflammation, oxidative damage and fibrotic effect.…”
mentioning
confidence: 99%